Shared molecular mechanisms regulate multiple catenin proteins: canonical Wnt signals and components modulate p120-catenin isoform-1 and additional p120 subfamily members - Hong, Ji Yeon (Company of Biologists, 2010)
Wnt signaling pathways have fundamental roles in animal development and tumor progression. Here, employing Xenopus embryos and mammalian cell lines, we report that the degradation machinery of the canonical Wnt pathway modulates p120-catenin protein stability through mechanisms shared with those regulating β-catenin. For example, in common with β-catenin, exogenous expression of destruction complex components, such as GSK3β and axin, promotes degradation of p120-catenin. Again in parallel with β-catenin, reduction of canonical Wnt signals upon depletion of LRP5 and LRP6 results in p120-catenin degradation. At the primary sequence level, we resolved conserved GSK3β phosphorylation sites in the amino-terminal region of p120-catenin present exclusively in isoform-1. Point-mutagenesis of these residues inhibited the association of destruction complex components, such as those involved in ubiquitylation, resulting in stabilization of p120-catenin. Functionally, in line with predictions, p120 stabilization increased its signaling activity in the context of the p120–Kaiso pathway. Importantly, we found that two additional p120-catenin family members, ARVCF-catenin and δ-catenin, associate with axin and are degraded in its presence. Thus, as supported using gain- and loss-of-function approaches in embryo and cell line systems, canonical Wnt signals appear poised to have an impact upon a breadth of catenin biology in vertebrate development and, possibly, human cancers.